CANADA : Foreign Extraterritorial Measures Act incorporating the amendments countering the U.S. Helms-Burton Act. (1997)
Presents recent amendments to Canada's Foreign Extraterritorial Measures Act, the thrust of which is to provide tools to Canadians to protect themselves from Helms-Burton litigation in respect of property interest that they might have in Canada.
DC